2020
DOI: 10.2147/phmt.s217475
|View full text |Cite
|
Sign up to set email alerts
|

<p>Systematic Review of <em>Kingella kingae</em> Musculoskeletal Infection in Children: Epidemiology, Impact and Management Strategies</p>

Abstract: Kingella kingae, a pathogen often responsible for musculoskeletal infections in children is the most common cause of septic arthritis and osteomyelitis in children 6 to 36 months of age. The aim of this study was to perform a systematic review of previous studies to determine the proportion of K. kingae in bacteriologically proven musculoskeletal infections among the pediatric population. A secondary objective was to describe the diagnostic strategies and outcome of patients with musculoskeletal infections cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…Among SA, 82% was KK-SA. The estimated incidence of bone and joint infections in children in France is 10 per 100,000 children, with KK accounting for 30% of bone and joint infections in children and up to 80% in children younger than 4 years of age 5,7,9,10,28 . Compared to the literature, our cohort had a higher rate of SA, with KK being implicated in the vast majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Among SA, 82% was KK-SA. The estimated incidence of bone and joint infections in children in France is 10 per 100,000 children, with KK accounting for 30% of bone and joint infections in children and up to 80% in children younger than 4 years of age 5,7,9,10,28 . Compared to the literature, our cohort had a higher rate of SA, with KK being implicated in the vast majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…These OMV's are hemolytic and leukotoxic in an in vitro model and internalized by synoviocytes inducing the synthesis of granulocytemacrophage colony stimulating factor (GM-CSF) and interleukin 6 (IL-6), likely representing the in vivo immunitary response in joint infections [15]. K. kingae has been recognized as a leading cause of septic arthritis and osteomyelitis in children less than 4 years old, usually with no underlying medical conditions [3,4]. Other rare primary manifestations in pediatric population are: Pneumonia, endocarditis, soft tissue infection, endophtalmitis, orbital cellulitis, and meningitis [1,2,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…K. kingae is currently recognized as the most common etiology of septic arthritis and osteomyelitis in children between the ages of 6 and 48 months. More rarely, it can cause complicated endocarditis, meningitis, ocular infections, pericarditis, peritonitis, and pneumonia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…K. kingae infections seem to be closely correlated to children’s ages. In a meta-analysis, Wong et al reported 47.6% of patients under 48 months of age were diagnosed with K. kingae BJI infections [ 4 ]. In this study, 55.6% of children were aged 6 to 48 months, and 14.8% (4/27) were under 6 months, 2 of them were aged < 1 month, with no history of trauma or unusual infections, and no warning signs of immunosuppression were found.…”
Section: Discussionmentioning
confidence: 99%
“…Using culture-based diagnostic methods in our hospital, we frequently observe negative cultures in pediatric BJI, and actually, we have no local data on the involvement of K. K in this infection type. It was reported that K. kingae represented 30.8% (711/2308) of pediatric cases with culture and/or PCR proven musculoskeletal infections [ 4 ]. Recently, improvement of nucleic acid amplification assay targeting either the rtx operon or the groEL gene (also known as cpn60 ) allowed a further increase in the diagnostic capability for pediatric K. kingae BJI [ 5 ].…”
Section: Introductionmentioning
confidence: 99%